Teachers’ Strategies in ESP Learning Program in Indonesia: A Comparative Study - Suharyanto Suharyanto (JELITA, 2024)
This research article examines various strategies utilized by English teachers in English for Specific Purposes (ESP) learning programs in Indonesia, focusing on the Social and Science study programs. The study used a qualitative research design to conduct in-depth interviews with 25 English teachers, which aim to investigate and compare the pedagogical approaches used to satisfy the unique linguistic and contextual requirements of these two academic disciplines. Through purposive sampling, English teachers from both Social and Science study programs participate in semi-structured interviews, providing rich insights into their instructional methods. The purpose of the qualitative analysis is to reveal trends, similarities, and differences in the strategies used, providing a detailed understanding of the complexities of ESP teaching methods. The findings reveal illumination on the specific strategies employed by English teachers in the Social and Science study programs, demonstrating how these strategies are shaped by curriculum complexity and the backgrounds of the learners. The comparative study highlights the significance of pedagogical techniques tailored to individual contexts and serves as a basis for making well-informed decisions in curriculum development and teacher training. This study has wider implications for improving English for Specific Purposes (ESP) learning programs in Indonesia and adds to the continuing discussion on effective language teaching. This study also provides helpful recommendations for educators, curriculum developers, and policymakers aiming to enhance language learning experiences in ESP environments.